Introducing blended learning: An experience of uncertainty for students in the United Arab Emirates - Linzi J. Kemp (Association for Learning Technology, 2013)
The cultural dimension of Uncertainty Avoidance is analysed in this study of an introduction to blended learning for international students. Content analysis was conducted on the survey narratives collected from three cohorts of management undergraduates in the United Arab Emirates. Interpretation of certainty with blended learning was found in: student skills with technology; student acknowledgement of course organisation; and student appreciation of online feedback. Uncertainty with the introduction of blended learning was found: when membership was assigned for group work, higher quality research methods were introduced; where course structure lacked detail, increased time was required for new and different online activities. These international students, from countries with a high score on Uncertainty Avoidance, exhibited that dimension when introduced to blended learning. The implications of these findings are discussed, and strategies suggested for introducing blended learning to international students. The limitations of the study are considered, and a direction for future research is suggested. This is the first study on undergraduates in the Middle East for the effects of a cultural dimension when introducing blended learning. The findings increase the body of knowledge that relates to learning technology in the international business classroom.